Professional development in teaching English - Shunkeyeva, S.A.; Yeskazinova, Zh.A. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article deals with training of highly qualified and competitive, with a sense of responsibility staff in higher educational institutions of the country due to the political and social — economic realities of social development. Under the state program offers the optimal ways to improve the professional development of teachers in leading foreign universities. The authors discussed the issues of improving information literacy, culture and competencies of teachers of foreign languages.
Ағылшын тілін оқытуда кəсіби даму
Профессиональное развитие в преподавании английского языка
Keywords: professional development; the Bologna process; self-awareness; qualified; competitive; information and communication technology; the University system; the optimal ways; training; teachers of foreign languages